Influence of non-invasive anatomical versus functional testing on physician certainty score among patients assessed within a rapid access chest pain clinic. (3rd October 2022) - Nguyen, D; Kalathil, S; Shiekh, I; Rajwani, A; Alcock, R; Schultz, C; Hillis, G; Spiro, J
Abstract: Background: Recently, rapid access chest pain clinics (RACPC) have been shown to improve clinical and economic efficiency, with some well-established models adopting non-invasive anatomical testing (CTCA) as a universal first test. Physician certainty over the presence of significant coronary artery disease (CAD) and that symptoms are likely secondary to CAD, may influence management decisions. Data directly comparing the performance of anatomical versus functional testing, in regards to their influence on physician certainty scores, remains sparse. Purpose: To assess the influence of non-invasive anatomical versus functional testing on physician certainty among patients attending a RACPC. Methods: Patients attending our RACPC were invited to participate. Recruitment to the research registry was via written consent. Registry patients undergoing non-invasive anatomical (CTCA) or functional testing (myocardial perfusion imaging (MPS), exercise treadmill test (ETT) or stress echo (SE)) were included in the current analysis. Physician certainty scores (yes/likely/unlikely/no) were generated at baseline (pre-test) and post-test for all registry patients for (1) the presence of CAD and (2) angina secondary to CAD. Change in physician certainty (frequency and direction) post-test was identified and analysed to determine the influence of each testing modality. Results: Between December 2015 and October 2021, 2541 patients attended RACPC, with 1542 patients recruited to the registry; mean age 57±12 years, 49% male, 16% typical angina, 30% atypical angina and 54% with non-anginal chest pain. Non-invasive anatomical or functional testing was performed in 1223 (79%) registry patients, with paired (pre and post-test) physician certainty scores available in 1184 (97%); 665 (56%) CTCA, 243 (21%) MPS, 210 (18%) ETT and 66 (5%) SE. Compared with functional testing, CTCA demonstrated a greater frequency of change in physician certainty scores for (1) presence of CAD (92% vs 58%, p<0.001) and (2) angina secondary to CAD (74% vs 61%, p<0.001), Figure 1. In addition, anatomical testing was also associated with greater differentiation in physician certainty for the presence of CAD; increased certainty, 47% vs 21% (p<0.001); decreased certainty, 44% vs 35% (p<0.01), with no change in certainty observed in only 8% anatomical vs 43% functional testing (p<0.001). Certainty for angina due to CAD was similar; increased certainty, 10% vs 8% (p=0.45); decreased certainty, 64% vs 53% (p<0.001); and no change 26% vs 38% (p<0.001), Figure 2. Conclusion: Compared to functional testing, non-invasive anatomical testing resulted in greater frequency of change and increased differentiation of physician certainty. These observations suggest that non-invasive anatomical testing within a RACPC setting may significantly enhance diagnostic confidence, which may help guide management decisions. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): State Health Research Advisory Council (SHRAC)- Western Australia